Usability Analysis of MSME Business Accounting Applications Based on User Retention Using ISO 9241-11 - Adilawati, Lega; Aini, Qurrotul; Nuryasin, Nuryasin (INTENSIF: Jurnal Ilmiah Penelitian dan Penerapan Teknologi Sistem Informasi, 2023)
BukuWarung has been known as a MSME’s bookkeeping application in Indonesia. As the features developed, there were disappointed responses from Playstore reviews, social media, and research interviews who complained about the usability aspect of this application, thus triggering the desire for users to stop using the application. This condition motivates the author to assess the impact level of usability in aspects of Effectiveness, Efficiency, and Satisfaction on user retention. This study used a partial least square–structural equation model method. The total of 248 user samples was obtained using simple random sampling and voluntary response techniques. The research uses CSUQ, as well as questions for user retention. For data testing used Ms. Excel and SmartPLS version 3.3.3. According to the measurement model, 7 of 22 all variables were deleted. This study proves that Effectiveness, Efficiency, and Satisfaction have a positive and significant effect of up to 74.8% on user retention. However, the size of influence and relative influence is weak on user retention. User retention indicators affected by usability are increasing purchases as tenure grows, customer referrals, and premium prices. The implication for BukuWarung is to conduct usability testing on each feature.